Synergist using incineration fly ash to improve the early-strength performance of quick-setting agent in low-temperature and stagnant water environment, preparation method and application thereof

By using the synergistic effect of incineration fly ash with sulfoaluminate cement and exciter, the prepared synergist significantly improves the pro-setting and early strength performance of the axial settling agent in low temperature and stagnant environments, solving the problem of degradation of the axial settling agent in the low temperature environment in the prior art, achieving faster settling time and higher early strength.

CN117945684BActive Publication Date: 2025-04-15安徽海螺环保集团有限公司
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410068242.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-17
Publication Date
2025-04-15
Estimated Expiration
2044-01-17

AI Technical Summary

Technical Problem

In low temperature and stagnant environments, the pro-condensation and early strength performance of existing accelerators has significantly decreased, resulting in an extended set time of sprayed concrete and low early strength, which affects the construction process.

Method used

A synergistic effect of incineration fly ash, sulfoaluminate cement and exciter is used to prepare a synergist to improve the premature performance of the accelerator in low temperature and stagnant water environments.

Benefits of technology

The clean slurry setting time of aluminum sulfate-based alkali-free liquid accelerator in low temperature environment is significantly shortened, the early compressive strength is improved, and construction costs are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004668972280000071
    Figure BDA0004668972280000071
  • Figure BDA0004668972280000081
    Figure BDA0004668972280000081
  • Figure BDA0004668972280000091
    Figure BDA0004668972280000091
Patent Text Reader

Abstract

The present invention provides a synergist for improving the early-strength performance of an accelerator using incineration fly ash in a low-temperature and stagnant water environment, and a preparation method and application thereof. The raw materials include: 35-55% incineration fly ash, 35-50% sulphoaluminate cement, and 5-15% activator. According to the principle that the low-temperature environment affects the early-strength performance of the accelerator, the present invention uses the synergistic effect of incineration fly ash and a variety of accelerators to improve the early-strength performance of the accelerator under low-temperature and stagnant water conditions, thereby achieving the purpose of improving the early performance of shotcrete. At the same time, the waste incineration fly ash can be used to realize the resource utilization of solid waste. The preparation process is simple, the use is convenient, and the construction and maintenance cost of shotcrete in a low-temperature environment is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the fields of tunnel and underground engineering and concrete, and in particular to a synergist that uses incineration fly ash to improve the early-strengthening performance of an accelerator in a low-temperature and stagnant water environment, and a preparation method and application thereof. Background Art

[0002] At present, when the liquid accelerator is tested with reference to the national standard GB / T 35159-2017, its addition time is significantly different from the actual construction addition time. When the performance of the accelerator is tested in the laboratory, the liquid accelerator is added immediately after the cement paste is mixed. However, in the actual construction process, the concrete is transported from mixing to the construction site and then reacts with the accelerator. The time period for adding the accelerator is significantly different from that for laboratory testing, resulting in differences between the effect of the accelerator tested in the laboratory and the effect of the accelerator in on-site construction. This is mainly manifested in the late addition period (water stagnation time), which significantly prolongs the setting time of the cement paste mixed with the accelerator. Especially in winter construction in northern regions, the early strength performance of the accelerator in the low-temperature stagnant water environment is significantly reduced, resulting in a prolonged setting time and low early strength of the shotcrete using the accelerator, thus affecting the construction process. At present, to improve the early effect of the accelerator in a low-temperature environment, the solution of increasing the temperature of the concrete mixture and the curing temperature is generally adopted, which will increase the construction cost.

[0003] At present, although there are relevant patents for improving the accelerator under low temperature environment, such as the patent with publication number CN 110615638A published on December 27, 2019, which discloses a low temperature resistant liquid alkali-free accelerator and its preparation method, the technical scheme adopted is: aluminum sulfate 40-50%, alcohol amine 5-10%, stabilizer 0.01-0.05%, enhancer 4-6%, modified nanomaterial 1-2%, pH adjuster 1-2%, water 29.95-48.99%. The patent with publication number CN114573263A published on June 3, 2022 discloses an alkali-free accelerator suitable for spraying construction under low temperature conditions and its use method, which is composed of FSA material (powder) and FSB material (liquid), wherein the FSA material contains silica fume, metakaolin and calcium acetate; the FSB material contains aluminum oxide, sulfur trioxide, NOx and H2O. The patent with publication number CN115368051A published on November 11, 2022, discloses an antifreeze-type quick-setting agent, its preparation method and shotcrete, and the raw materials are: 50-60% aluminum sulfate, 2-5% inorganic salt, 0.5-1.0% stabilizing component, 1-3% antifreeze component, 2-5% organic complexing component, 0.005-0.02% inorganic nano component, and the rest is water. There is also a patent with publication number CN113860787A published on December 31, 2021, which discloses a two-component alkali-free quick-setting agent suitable for plateau cold areas and a method of use. The disclosed two-component alkali-free quick-setting agent includes a fast-hardening component A and a coagulant component B, and the mass ratio of the two is 70-80:20-30. Among them, the quick-hardening component A is a powder material, mainly composed of tricalcium aluminate (C3A), calcium hydroxide (CH), and hemihydrate gypsum (CaSO4﹒0.5H2O); the accelerating coagulant component B is a liquid material, mainly composed of polyaluminum sulfate (PAS), triethanolamine (TEOA), lithium sulfate (Li2SO4), lactic acid (HL) and water.

[0004] The above existing technologies all have limitations, which are mainly manifested in that they only target specific alkali-free liquid accelerating setting agent preparation processes, such as: adjusting the raw materials of the accelerating setting and early strength component in the synthesis process, and the synergy of the early strength powder and the liquid accelerating setting and early strength component, so as to improve the accelerating setting and early strength performance of the accelerating setting agent under low temperature environment. However, they fail to solve the defects of the currently available accelerating setting agent products, such as: the common problems of slow setting time and low early strength under low temperature stagnant water environment.

[0005] Therefore, there is an urgent need to develop a synergist to improve the early-strengthening performance of the quick-setting agent in low-temperature environments and stagnant water conditions. Summary of the invention

[0006] The purpose of the present invention is to provide a synergist for improving the early strength performance of an accelerator using incineration fly ash under low temperature and stagnant water conditions and a preparation method thereof. Based on the principle that the low temperature environment affects the early strength performance of the accelerator, the synergistic effect of incineration fly ash and a variety of accelerators is used to improve the early strength performance of the accelerator under low temperature and stagnant water conditions, thereby achieving the purpose of improving the early performance of shotcrete. At the same time, the waste incineration fly ash can be used to realize the resource utilization of solid waste. The preparation process is simple, the use is convenient, and the construction and maintenance cost of shotcrete in a low temperature environment is reduced.

[0007] Another object of the present invention is to provide an application of a synergist that uses incineration fly ash to improve the early-strength performance of a quick-setting agent under low temperature and stagnant water conditions. The synergist can be used for shotcrete to improve the early-strength performance of a quick-setting agent under low temperature and stagnant water conditions, thereby achieving the purpose of improving the early performance of shotcrete.

[0008] The specific technical solutions of the present invention are as follows:

[0009] A synergist that uses incineration fly ash to improve the early-strengthening performance of an accelerator in a low-temperature and stagnant water environment, comprising the following raw materials in percentage by weight:

[0010] Incineration fly ash 35-55%, sulphoaluminate cement 35-50%, activator 5-15%, totaling 100%.

[0011] The main components of the incineration fly ash are CaO content of 50-70%, MgO of 2-5%, SiO2 of 5-10%, and SO3 of 10-15%.

[0012] The sulphoaluminate cement is selected from fast-hardening sulphoaluminate cement 42.5.

[0013] The activator is one or more of calcium formate, lithium silicate or aluminum formate.

[0014] The present invention provides a method for preparing a synergist that uses incineration fly ash to improve the early strength performance of an accelerator in a low temperature and stagnant water environment, specifically comprising:

[0015] Mix all the raw materials evenly according to the formula.

[0016] Preferably, a forced powder mixer is used to mix the raw materials.

[0017] Preferably, the mixing time is 15 min.

[0018] The invention provides an application of a synergist that uses incineration fly ash to improve the early-strength performance of an accelerator in a low-temperature and stagnant water environment, and the synergist is used for shotcrete.

[0019] The synergist that uses incineration fly ash to improve the early-setting performance of the accelerator in a low-temperature and stagnant water environment is used in combination with the accelerator when it is used for shotcrete;

[0020] The dosage of the synergist is 6-10% of the mass of the cementitious material in the shotcrete.

[0021] The dosage of the accelerating agent is 7% of the mass of the cementitious material in the shotcrete.

[0022] Waste incineration fly ash is a solid waste with low cost. It contains a large amount of CaO, which can synergistically enhance the accelerating effect of the accelerator. In addition, the incineration fly ash contains SO3, which has a potential accelerating effect under the stimulation of the accelerator. Both of the above can be used with the accelerator to effectively enhance its early strength effect under low temperature and stagnant water conditions. Therefore, the use of waste incineration fly ash to prepare shotcrete enhancers to enhance the effect of accelerators under special environments has potential market prospects.

[0023] Compared with the prior art, the synergist provided by the present invention combines the composition characteristics of waste incineration fly ash, and the calcium oxide, alkaline substances, sulfates and other components contained therein can promote the hydration of minerals in cement, accelerate the reaction, and prepare the accelerator synergist through excitation and coagulation synergistic preparation, and the preparation process is simple, the cost is low, and it is easy to use. The synergist can significantly shorten the setting time of the aluminum sulfate-based alkali-free liquid accelerator slurry under low temperature environment and in the presence of stagnant water time, improve the early compressive strength, and does not affect the workability of fresh concrete. In addition, the synergist has the effect of reducing the effect of stagnant water on the coagulation performance of the aluminum sulfate-based alkali-free liquid accelerator. DETAILED DESCRIPTION

[0024] In order to illustrate the advantages and features of the present invention in detail, the present invention is described in detail in conjunction with the following embodiments.

[0025] The main components of the incineration fly ash used in the present invention are 50-70% CaO, 2-5% MgO, 5-10% SiO2 and 10-15% SO3; the sulphoaluminate cement is selected from fast-hardening sulphoaluminate cement 42.5.

[0026] Example 1

[0027] A method for preparing a synergist that uses incineration fly ash to improve the early-strength performance of an accelerator in a low-temperature and stagnant water environment, specifically comprising the following steps: weighing 50% by mass of incineration fly ash, 45% by mass of rapid-hardening sulphoaluminate cement, and 5% by mass of calcium formate, and mixing them evenly using a forced powder mixer for 15 minutes to obtain the synergist.

[0028] Example 2

[0029] A method for preparing a synergist that uses incineration fly ash to improve the early-strength performance of a quick-setting agent in a low-temperature and stagnant water environment, specifically comprising: weighing 50% by weight of incineration fly ash, 45% by weight of fast-hardening sulphoaluminate cement, and 5% by weight of lithium silicate, and mixing them evenly using a forced powder mixer for 15 minutes to obtain the synergist.

[0030] Example 3

[0031] A method for preparing a synergist that uses incineration fly ash to improve the early-strength performance of a quick-setting agent in a low-temperature and stagnant water environment, specifically comprising: weighing 55% by mass of incineration fly ash, 40% by mass of fast-hardening sulphoaluminate cement, and 5% by mass of aluminum formate, and mixing them evenly using a forced powder mixer for 15 minutes to obtain the synergist.

[0032] Example 4

[0033] A method for preparing a synergist that uses incineration fly ash to improve the early-strength performance of an accelerator in a low-temperature and stagnant water environment, specifically comprising the following steps: weighing 50% by mass of incineration fly ash, 40% by mass of fast-hardening sulphoaluminate cement, 5% by mass of calcium formate, and 5% by mass of lithium silicate, and mixing them evenly using a forced powder mixer for 15 minutes to obtain the synergist.

[0034] Example 5

[0035] A method for preparing a synergist that uses incineration fly ash to improve the early-strength performance of an accelerator in a low-temperature and stagnant water environment, specifically comprising: weighing 45% by mass of incineration fly ash, 45% by mass of fast-hardening sulphoaluminate cement, 5% by mass of calcium formate, 2.5% by mass of lithium silicate, and 2.5% by mass of aluminum formate, and mixing them evenly using a forced powder mixer for 15 minutes to obtain the synergist.

[0036] Example 6

[0037] A method for preparing a synergist that uses incineration fly ash to improve the early-strength performance of an accelerator in a low-temperature and stagnant water environment, specifically comprising the following steps: weighing 40% by mass of incineration fly ash, 50% by mass of fast-hardening sulphoaluminate cement, 5% by mass of calcium formate, and 5% by mass of lithium silicate, and mixing them evenly using a forced powder mixer for 15 minutes to obtain the synergist.

[0038] Example 7

[0039] A method for preparing a synergist that uses incineration fly ash to improve the early-strength performance of an accelerator in a low-temperature and stagnant water environment, specifically comprising: weighing 40% by mass of incineration fly ash, 50% by mass of fast-hardening sulphoaluminate cement, 5% by mass of calcium formate, 2.5% by mass of lithium silicate, and 2.5% by mass of aluminum formate, and mixing them evenly using a forced powder mixer for 15 minutes to obtain the synergist.

[0040] Test 1: Select a commercially available aluminum sulfate-based alkali-free liquid accelerator to measure the setting time and compressive strength of the mortar mixed with the alkali-free liquid accelerator under low temperature conditions.

[0041] Test 2: An alkali-free liquid setting accelerator was selected for use with the synergists of Examples 1 to 7, respectively. The synergist was first added in an amount of 6 to 10% of the mass of the cementitious material. Then, the alkali-free liquid setting accelerator was added at 7% of the mass of the cementitious material. The setting time of the net slurry mixed with the alkali-free liquid setting accelerator and the compressive strength of the mortar under low temperature conditions were measured.

[0042] Performance evaluation and usage of the synergist: Add 6-10% of the mass of the cementitious material. The performance test of the synergist shall be carried out in accordance with the national standard GB / T 35159-2017 "Accelerator for Shotcrete", in which the dosage of the alkali-free accelerator is 7% of the mass of the cementitious material.

[0043] Performance testing and use of synergist in low temperature and stagnant water environment: All raw materials are stored in a low temperature environment of 5℃ for 24h, and the synergist is 6-10% of the cementitious material dosage. The stirred pure slurry is stagnant for 30min (skip this step when testing without stagnant water conditions), and the alkali-free liquid accelerator is added to test the setting time of the pure slurry. In addition, mortar specimens are prepared in the same way, and cured to the corresponding age at the corresponding ambient temperature for compressive strength testing. The dosage of alkali-free accelerator used in the test is 7% of the mass of the cementitious material.

[0044] The above test results are shown in Table 1.

[0045] Table 1 Test results of synergists in various embodiments

[0046]

[0047]

[0048] Note: The cement used is the base cement.

[0049] The results in Table 1 show that the addition of alkali-free liquid accelerator to the paste in low temperature environment prolongs the setting time of the paste and reduces the early compressive strength of the mortar, while the synergistic addition of synergist and accelerator can significantly shorten the setting time of the paste and improve the 1d and 28d compressive strength of the mortar.

[0050] Test 3: Taking into account the actual situation of projects in northern China, in the presence of low-temperature stagnant water, a commercially available aluminum sulfate-based alkali-free liquid accelerator was selected to measure the setting time and compressive strength of the mortar mixed with the alkali-free liquid accelerator under low-temperature stagnant water and commercially available Kezhijie high-efficiency water reducer conditions.

[0051] Test 4: Alkali-free liquid accelerator was selected for use with the synergist of Examples 1 to 7 respectively. The synergist and Kezhijie high-efficiency water reducer were first added. The synergist dosage was 6-10% of the mass of the cementitious material, and the water reducer dosage was 1% of the mass of the cementitious material. Then, the alkali-free liquid accelerator was added at 7% of the mass of the cementitious material. The setting time test of the net slurry added with the alkali-free liquid accelerator under the conditions of water reducer and stagnant water and the compressive strength of the mortar were measured.

[0052] The test results of the above test 3 and test 4 are shown in Table 2.

[0053] Table 2 Test results of various embodiments

[0054]

[0055]

[0056] Note: The cement used is the base cement

[0057] The results in Table 2 show that under the conditions of low temperature stagnant water and water reducing agent, the setting time of the pure slurry added with alkali-free liquid quick-setting agent is prolonged and the early compressive strength of the mortar is reduced, while the setting time of the pure slurry is significantly shortened after the synergistic addition of the synergist.

[0058] The results in Tables 1 and 2 show that the synergist prepared with incineration fly ash as the main raw material can improve the early strength performance of aluminum sulfate-based alkali-free liquid accelerator under low temperature conditions. Under the conditions of simulated construction water stagnation and water reducing agent, the setting time of the slurry mixed with the synergist and the compressive strength of the mortar were measured, indicating that the synergistic addition of the synergist can improve the early strength performance of aluminum sulfate-based alkali-free liquid accelerator under low temperature water stagnation conditions.

Claims

1. A synergist for improving the early-strengthening performance of an accelerated setting agent under low temperature and stagnant water conditions using incineration fly ash, characterized in that: The synergist comprises the following raw materials in percentage by weight: Incineration fly ash 35~55%, sulphoaluminate cement 35~50%, activator 5~15%; The main components of the incineration fly ash are CaO content of 50-70%, MgO of 2-5%, SiO2 of 5-10%, and SO3 of 10-15%.

2. The synergist according to claim 1, characterized in that The sulphoaluminate cement is selected from fast-hardening sulphoaluminate cement 42.

5.

3. The synergist according to claim 1, characterized in that The activator is one or more of calcium formate, lithium silicate or aluminum formate.

4. A method for preparing a synergist for improving the early strength performance of an accelerator using incineration fly ash in a low temperature and stagnant water environment as claimed in any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: uniformly mixing the raw materials according to the formula amount to obtain the product.

5. The preparation method according to claim 4, characterized in that: Mixing time 15 min.

6. An application of a synergist for improving the early strength performance of an accelerated setting agent using incineration fly ash in a low temperature and stagnant water environment as claimed in any one of claims 1 to 3, characterized in that: For shotcrete.

7. The use according to claim 6, characterized in that: When the synergist is used for shotcrete, it is compounded with an accelerator.

8. The use according to claim 6 or 7, characterized in that: The dosage of the synergist is 6-10% of the mass of the cementitious material.

Citation Information

Patent Citations

  • Low-temperature-resistant liquid alkali-free accelerator and preparation method thereof

    CN110615638A

  • Two-component alkali-free accelerator suitable for plateau cold regions and using method

    CN113860787A

  • Alkali-free setting accelerator suitable for spraying construction under low-temperature condition and use method of alkali-free setting accelerator

    CN114573263A

  • Anti-freezing accelerator, preparation method thereof and sprayed concrete

    CN115368051A

  • Quick-setting gel material and preparation method thereof

    CN103833246A